Compositional dependence of optical transition energies in highly mismatched Zn1−xCdxTe1−yOy alloys. (21st January 2016) - Tanaka, Tooru; Mizoguchi, Kosuke; Terasawa, Toshiki; Okano, Yuuki; Saito, Katsuhiko; Guo, Qixin; Nishio, Mitsuhiro; Man Yu, Kin; Walukiewicz, Wladek
Abstract: Highly mismatched Zn1− x Cd x Te1− y O y layers with a wide range of Cd and O compositions of 0–0.7 and 0.005–0.02, respectively, were grown by molecular beam epitaxy for the application of intermediate band solar cells. The electron transition energies from the valence band (VB) to E − and E + bands decreased with increasing Cd content. The variation of the transition energies was consistent with the theoretical calculation based on the band anticrossing model. The magnitude of the optical absorption due to electron transitions from the VB to E − band was strongly dependent on the Cd content because of the changing character of the E − band.